TINJAUAN SINGKAT TENTANG METODE ADSORPSI MENGGUNAKAN BAHAN KONVENSIONAL UNTUK PENGOLAHAN AIR ASAM TAMBANG - Wibowo, Yudha Gusti; Tsabitah, Natasya; Pratiwi, Cantika; Nur'ani, Herlina; Irene, Rilis; Syahnur, Mirza; Al-azizah, Putri; Yudhoyono, Aryo; Wijaya, Candra; Bonifasius; Kholivia; Dody Oktantiyo S; Anis (Indonesian Mining Journal, 2024)
Acid mine drainage (AMD) is a highly dangerous form of water pollution results from coal mining activities. AMD is characterized by its high concentration of heavy metals and low pH levels, which have been linked to various health problems, including skin disease, cancer, and poisoning. This paper presents a comprehensive review of the available information on the AMD and its alternative low-cost treatment methods. One such method is adsorption, an eco-friendly and cost-effective approach to treating the AMD. This review draws on 99 published papers as the sources that provide a comprehensive overview of the AMD sources and problems worldwide. This study explores the potential of conventional materials, such as activated carbon, biochar, and other materials for treating the AMD. A special section on conventional materials is well-detailed and provides valuable insights into their effectiveness. It is essential to explore the alternative treatment methods that are both environmentally friendly and cost-effective. This review provides valuable insights in this regard. By using the low-cost and sustainable methods, we can effectively treat AMD and reduce its impact on the environment and human health.